Implementation of Project-Based Learning Model in Social Studies Subjects at Islamic Junior High School - Ahmad Irfan Fanani; Mohammad Na'im; Sukidin (International Journal of Contemporary Sciences (IJCS), 2024)
This study aims to explore the implementation of the Project Based Learning (PjBL) learning model in learning Social Sciences (IPS) at MTs Zainul Hasan 4 Boto Lumbang, Probolinggo Regency. The research method used is qualitative with a case study approach. Data were collected through direct observation, in-depth interviews with teachers and students, and document analysis related to the implementation of PjBL. The results showed that the implementation of PjBL at MTs Zainul Hasan 4 had a positive impact on student learning engagement and motivation. Students are more actively participating in the learning process through projects that are relevant to real life, which allows them to develop critical thinking, collaboration and problem-solving skills. In addition, PjBL also helps students connect theory with practice, thus deepening their understanding of social studies concepts